UJI BENDING DAN APLIKASI WPS PADA PLAT KAPAL TANKER DENGAN GAP 2 MM DI PT. DAYA RADAR UTAMA LAMPUNG - Yulli Indriyanti; Kurniawati Oktarina; Suzi Heti Kurnia (LPPM Politeknik Jambi, 2020)
The ship production process is largely a welding work. About one-third of the total number of jobs in the construction stage is regulated Welding Procedure Specification (WPS) which is regulates welding rules such as class material, electrodes, how to weld the bevel shape long distance bevel (gap) and slope angle. Based on the WPS used of construction HN 309 Tanker Ship the length of the bevel distance (gap) in welding SMAW is 2,63 mm. Bending tests are performed to regulate strength of materials due to loading without causing deformation. This research study aims to determine the bending strength (quality) of the welders is 1 mm plate with variants of are 100 A 120 A and 140 A. The welding method ASTM A36 plate which is do bending test to using MTS landmark ASTM E 190-2003. The flexural strength of bending test from the three specimens based on current variation is the value of current strength 140 A is best compared to the current strength of 120 A and 100 A, the value of 140 current strength is 1.76107649 kN /mm2, current value of 120 A is 1,50230752 KN/mm2 and 100 A current strength of 1,44976202 kN /mm2 with a linear regression value is 0,872. So that the 11 mm plate welding procedure with a 2 mm gap can be used in the ship building production process.